A Scientometric Systematic Review of Entrepreneurial Wellbeing Knowledge Production - Contreras-Barraza, Nicolás; Espinosa-Cristia, Juan Felipe; Salazar-Sepulveda, Guido; Vega-Muñoz, Alejandro; Ariza-Montes, Antonio (Frontiers in Psychology, 2021)
This article presents a scientometric study regarding entrepreneurship and its relationship with wellbeing. The study presents a systematic review and measures impact and relational character to identify the relevance of countries, research organizations, and authors in the field of entrepreneurial wellbeing. The study poses the following research questions: What is the nature of the evolution of scientific knowledge in the entrepreneurial wellbeing field? What is the nature of the concentration in terms of geographical distribution and co-authorship level of knowledge production in the entrepreneurial wellbeing field? What are the knowledge trends in knowledge production for entrepreneurial wellbeing literature? The contribution of this research is two-fold. First, in terms of methodology, it contributes study into the use of a more robust approach to search for the scientometric trends about entrepreneurship wellbeing in addition to the PRISMA review tools and the PICOS eligibility criteria. Secondly, the study presents research updates in the search for results for the last 2 years of knowledge production. This upgrade is particularly important in a research field that presents exponential growth, where 2019 and 2020 presented almost double the amount of knowledge production compared to 2017 and 2018.